2017
DOI: 10.2147/jpr.s131692
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of 0.75% ropivacaine instillation into subinguinal wound in patients after bilateral microsurgical varicocelectomy: a bi-center, randomized, double-blind, placebo-controlled trial

Abstract: ObjectiveTo evaluate the efficacy and safety of 0.75% ropivacaine instillation into inguinal wound in patients who have undergone bilateral microsurgical varicocelectomy.Patients and methodsEighty-five men who were screened for bilateral varicoceles from March 2015 to July 2016 were randomized for the treatment. All patients underwent inguinal varicocelectomy by general anesthesia. After ligation of the internal spermatic veins from the spermatic cord, additional delivery of testis through inguinal incision si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Cu et al . [ 16 ] studied the efficacy and safety of 0.75% ropivacaine instillation into inguinal wound on 55 patients who had undergone bilateral microsurgical varicocelectomy by general anesthesia. They found that VAS pain scores and Prince Henry Pain Score in the ropivacaine-instilled operative site were significantly lower compared to those obtained with placebo at 2, 4, and 8 h after surgery ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Cu et al . [ 16 ] studied the efficacy and safety of 0.75% ropivacaine instillation into inguinal wound on 55 patients who had undergone bilateral microsurgical varicocelectomy by general anesthesia. They found that VAS pain scores and Prince Henry Pain Score in the ropivacaine-instilled operative site were significantly lower compared to those obtained with placebo at 2, 4, and 8 h after surgery ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we evaluated the efficacy and safety of 0.75% ropivacaine instillation into inguinal wounds in patients who underwent bilateral microsurgical varicocelectomy [ 2 ]. Before repairing the external oblique aponeurosis, 6 mL of 0.75% ropivacaine or 6 mL of normal saline was instilled under the fascia and around the funiculus (spermatic cord) in a randomized and double-blind study design.…”
mentioning
confidence: 99%
“…Before repairing the external oblique aponeurosis, 6 mL of 0.75% ropivacaine or 6 mL of normal saline was instilled under the fascia and around the funiculus (spermatic cord) in a randomized and double-blind study design. Visual analogue scale (VAS) pain scores and the Prince Henry Pain Score (PHPS) were used for evaluating the operative sites at 1, 2, 4, and 8 hours and 7 days after surgery [ 2 ]. The VAS pain scores and PHPS at the ropivacaineinstilled operative sites were significantly lower than those in the placebo group at 2, 4, and 8 hours after surgery [ 2 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations